A long-term comparison of nighttime cluster events and daytime ion formation in a boreal forest - Mazon, Stephany Buenrostro; Kontkanen, Jenni; Manninen, Hanna E.; Nieminen, Tuomo; Kerminen, Veli-Matti; Kulmala, Markku (Finnish Environment Institute, 2016)
New particle formation (NPF) events are typically observed during daytime when photochemical oxidation takes place. However, nighttime nucleation mode particles have been observed across various locations only sporadically. We present 11 years (2003-2013) of air ion number size distribution data from the SMEAR II station in Hyytiala, Finland, where during a third of the nights a sub-3 nm negative (n = 1324 days) and positive (n = 1174 days) ion events took place. To investigate nocturnal clustering at sizes above the constant small ion pool, we defined cluster events (CE) as a nocturnal event with 2-3 nm ion concentrations reaching 70 cm-3 between 18:00 and 24:00 local time. CE (n = 221 days) were characterized by a rapid, 10-fold increase in the median 2-3 nm ion concentration from the start (similar to 10 cm(-3)) to the event peak (similar to 100 cm(-3)). Furthermore, small and intermediate ions during the CE, NPF events and nonevents were compared: while concentrations of 1.5-2 nm ions were the highest during CE (median 235 cm(-3)), as compared with the NPF events (96 cm(-3)) or the daytime and nighttime nonevents (similar to 20 cm(-3)), 3-7 nm ion concentrations increased notably only during NPF events (median 52 cm(-3)). Specifically, ion concentrations during CE decreased for sizes above-2.4 nm (<10 cm(-3)). In addition, 90% of CE proceeded either a NPF event (55%) or a undefined day (35%), and only 10% of them proceeded a daytime non-event. This study suggests a build-up of 0.9-2.4 nm ion clusters during CE nights (18:00-24:00) that equals or exceeds the ion concentration levels during daytime NPF, but unlike the latter, CE fail to activate and grow clusters > 3 nm in diameter in nighttime Hyytiald. Peer reviewed